Automatic Lock Door With Voice Commands On Arduino-Based Android - Tullah, Rahmat; Dul Hapid, Saca; Suwandara, Junando Akas (STMIK Bina Sarana Global, 2021)
The key has an important function in the security system on the door which is the access to enter the room. To unlock a door, we usually need a key to open or lock a door. The purpose of this paper is to provide comfort or convenience in opening or locking doors with a more sophisticated and efficient security system using voice commands on Android. Automatic lock doors with voice commands on Android are a development of room door locks that still use conventional keys. This research uses the Arduino microcontroller as the brain of the solenoid used to lock the door and the magnetic switch is used to detect movement at the door, SIM800L is used to send notification messages in the form of SMS to registered admins. The method used is the prototype method, the prototype provides an overview to the user how the work flow in the system to be built. Application and tool testing is carried out to determine the performance of the applications and tools designed on the proposed system. The result of this research is a prototype automatic lock door with voice commands on Android based on Arduino Uno.